E-Governance Aiding Good Governance : An Empirical Evidence in the Indian Context - Yadav, Rajesh Kumar; Bagga, Teena (Prabandhan: Indian Journal of Management, 2020)
The Bhagavad Gita indicates good governance as great leadership, dutifulness, and self-realization which are re-interpreted in the modern context. Good governance today has become a way of measuring how public institutions conduct public affairs and manage public resources in a preferred way. It is an accomplishment dependent on many factors and e-governance is one of them. Infact both, good governance and e-governance have different dimensions which impact each other in some way. Taking into consideration the available theoretical literature, a conceptual model was framed in-order to examine the association of these two in the Indian context. The secondary data available in Public Affairs Index report 2016 for good governance and Internet Readiness Index Report 2017 for the aspect of e-governance were used to test the hypotheses. Upon empirical validation of the hypothesized model, it was found that the two dimensions of E-governance, that is, E-Infrastructure and IT Environment were positively associated with good governance ; whereas, the other two dimensions of E-governance, that is, E-Participation and E-Services were found to be negatively associated with good governance. The study findings concluded that governments can promote good governance by enhancing the infrastructural and information technology components.